Fahrerintentionserkennung zur lichtbasierten Kommunikation mit Fußgängern - Reschke, Johannes (Spektrum der Lichttechnik, 2022)
Especially pedestrians rely on the interaction with other road users. The introduction of automated driving systems withdraws this communication from drivers and thus, vehicles need to interact with pedestrians. Therefore, multiple vehicle-pedestrian-communication concepts are evaluated. A driver intention prediction allows pedestrians to learn these newly introduced signals, while driver and vehicle communicate simultaneously.